Age and gender differences in fundamental motor skills (original version in English) - Jiménez Díaz, Judith (Escuela de Educación Física y Deportes - Universidad de Costa Rica, 2015)
Fundamental motor skills are the basis for participation in more advanced lifetime activities. Whereas considerable research has been reported on motor behavior of children, much less is known about performance in later years, especially adulthood. Therefore, the aim of this study was to examine age and gender differences on fundamental motor skills (FMS) ability across three age groups: children (M = 9.37 yr., SD = 1.26), adolescents (M = 14.80 yr., SD = 2.04) and young-adults (M = 19.88 yr., SD = 2.72). Participants (n = 114) were assessed on five locomotor skills (run, gallop, slide, hop, and distance jump) and five object control skills (bounce, catch, overhand throw, strike and kick) using the Test for Fundamental Motor Skills, which is a process-oriented instrument. ANOVA results comparing gender and group revealed no significant interactions. Moreover, main effects for group were found for three individual skills: galloping –adolescents and young-adults performed better than children (p < .01)–, throwing –children and adolescents performed better than young-adults (p < .01) –, and kicking –young-adults performed better than children and adolescents (p < .05)–. Also, we found main effects for gender for total FMS ability (p < .01), locomotor subscale (p < .05) and object control subscale (p < .01), and for six individual motor skills: run (p < .05), jump (p < .05), throw (p < .01), kick (p < .01), bounce (p < .01) and strike (p < .01); males outperformed females for all the skills. However, in view of total FMS ability, locomotor skills and object control skills results suggest similar performance across ages. Therefore, it is important to enhance fundamental motor skills at all ages, as an option to help individuals engage in physical activities.